A prospective study of wound complications in cancer breast surgery following neoadjuvant chemotherapy - Kumar, Ashok; Nathani, Neeraj; Kumar, Shishir (International Surgery Journal, 2018)
Background: Neoadjuvant chemotherapy is most of the time suitable for subset of the patients of breast cancer in Indian population. Neoadjuvant chemotherapy may be used to down stage a tumor that is inoperable in its current state, so that curative resection becomes feasible. But also, it can decrease size of operable primary tumour so that breast conserving surgery become possible which has better functional outcome and improves the quality of life. Therefore, there is a need to improve understanding of potential for post-operative complications in recipients of Neoadjuvant chemotherapy. Given that neutropenia is most common side effect of chemotherapeutics, this has raised concerns regarding the increased risk of post-operative complications. The objective of present study is to examine the risk of post-operative wound complications in patients receiving neoadjuvant chemotherapy for breast cancer. Methods: This study was conducted on 60 patients of breast carcinoma admitted for treatment to Nehru Hospital, BRDMC Gorakhpur for treatment during the period of July 2016-December 2017. Results: Seroma formation was most common complication observed in 20% (12/60) patients followed by superficial surgical site infection in 6.67% (4/60) patients, Deep surgical site infection in 2 patients (3.33%). Wound dehiscence in 2 (3.33%) patients. These data suggested that no obvious increase in complications in patients gone for neoadjuvant chemotherapy. Conclusions: Authors concluded that the rate of wound complications for breast cancer patients receiving Neoadjuvant chemotherapy is low. Seroma formation is the most frequent complication. Other complications can be avoided if proper preventive measures are taken. Smoking, hypertension, DM and obesity were associated with an increased risk of wound complications for patients undergoing BCS or MRM.